Pertumbuhan dan kelangsungan hidup ikan Nila (Oreochromis niloticus) yang diberi pakan komersil dengan penambahan Effective Microorganism-4 - Mokoginta, Laylah F.; Sinjal, Hengky J.; Pangemanan, Novie P.L.; Pelle, Wilmy E.; Solang, Jhonly (e-Journal BUDIDAYA PERAIRAN, 2022)
This study aimed to determine the effect of different doses of EM-4 in feed on the growth and survival of tilapia. This research was conducted at the Center for Freshwater Aquaculture (BPBAT) Tatelu. The study was carried out from June to August 2021. The experimental design used was a Completely Randomized Design (CRD) with 4 treatments and each treatment had 3 replications. The treatment used was Probiotic EM-4 with different doses consisting of: A: 0 ml/kg feed, B: 15 ml/kg feed, C: 20 ml/kg feed, D: 30 ml/kg feed. The results of the study used the Analysis of Variance (ANOVA) using the SPSS application (22). Giving different doses of EM-4 in the feed gave a significantly different effect on the absolute weight growth of tilapia, but the results also showed that the administration of different doses of EM-4 in solid had no effect on absolute length growth, daily length growth rate, FCR and tilapia survival. The treatment that had an effect on the absolute weight growth of tilapia was found in the treatment with a dose of EM-4 15 mL/kg of feed with an absolute weight growth of 23.89 g.